2018
DOI: 10.1016/j.cels.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Production of Protein-Complex Components Is Stoichiometric and Lacks General Feedback Regulation in Eukaryotes

Abstract: SUMMARY Constituents of multi-protein complexes are required at well-defined levels relative to each other. However, it remains unknown whether eukaryotic cells typically produce precise amounts of subunits, or instead rely on degradation to mitigate imprecise production. Here we quantified the production rates of multi-protein complexes in single- and multi-cellular eukaryotes using ribosome profiling. By resolving read-mapping ambiguities which occur for a large fraction of ribosome footprints and distort qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
124
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(136 citation statements)
references
References 56 publications
11
124
1
Order By: Relevance
“…This is consistent with a recent 399 comprehensive analysis showing that N-acetylation rarely acts as a degradation signal in 400 physiological conditions in yeast [37]. In agreement with these findings, a limited number of 401 subunits are physiologically synthesized in excess compared to stoichiometry and the 402 half-life of such subunits tends to be faster than that of proportionally synthesized subunits 403 [13,14]. Therefore, NATs-mediated dosage compensation may be a fail-safe mechanism that 404 is rarely and predominantly triggered by genetic perturbations or physiological overexpres-405 sion causing stoichiometric imbalance.…”
Section: Nats Contribute To Dosage Compensation In a Complex Manner 238supporting
confidence: 86%
“…This is consistent with a recent 399 comprehensive analysis showing that N-acetylation rarely acts as a degradation signal in 400 physiological conditions in yeast [37]. In agreement with these findings, a limited number of 401 subunits are physiologically synthesized in excess compared to stoichiometry and the 402 half-life of such subunits tends to be faster than that of proportionally synthesized subunits 403 [13,14]. Therefore, NATs-mediated dosage compensation may be a fail-safe mechanism that 404 is rarely and predominantly triggered by genetic perturbations or physiological overexpres-405 sion causing stoichiometric imbalance.…”
Section: Nats Contribute To Dosage Compensation In a Complex Manner 238supporting
confidence: 86%
“…Received April 10, 2019;revised version accepted May 13, 2019. Eukaryotes have a problem: Subunits of protein complexes are not encoded in operons. Although eukaryotes have evolved to coordinate expression of subunits of the same complex (Li et al 2014;Taggart and Li 2018), changes in gene dosage of a subset of subunits of a protein complex, transient gene copy number imbalances during DNA replication, or fluctuations in gene expression can disrupt this coordinate expression, leading to the production of complex subunits that lack their binding partners. These orphan subunits have the potential to misfold and cause proteotoxic stress.…”
mentioning
confidence: 99%
“…As a result, Class I target genes (the unconnected genes) show less-coordinated expression responses to WGD. Consistent with this hypothesis, Taggart and Li (2018) demonstrated that proteins in complexes with obligate stoichiometry are produced in proportion to their dosage and concluded that their expression levels are hard-wired by cis-regulatory 425 sequences.…”
mentioning
confidence: 79%
“…Multiple layers of post-transcriptional gene regulation could potentially result in imbalance at the protein level despite maintenance of balance at the gene dosage and/or transcriptional levels. Perform-475 ing similar analyses to those presented here, but that incorporate ribosome profiling (Taggart and Li 2018) and/or quantitative proteomic data, would be necessary to fully assess whether protein dosage is sufficiently linked with gene dosage for selection to act on gene copy number to preserve balance in protein complexes and signaling cascades. Nonetheless, although quantifying proteins would provide the most direct evidence for this important assumption, any influence of gene dosage 480 on protein abundance is presumably mediated by transcription, so the fact that the expected patterns are observed at the level of transcription attests to the efficacy of even these more indirect approaches and provides an important layer of support for the GBH.…”
mentioning
confidence: 99%